Development of educational material to subsidize the practice of physical education teachers in the working with hard of hearing students - Romera, Luciano Coelho; Carrit Delgado-Pinheiro, Eliane Maria [UNESP]; Santos, Flavia Rodrigues dos [UNESP]; Pinheiro, Osni Lazaro (Univ Federal Santa Maria, 2021)
In the educational context, there is a need for educational materials about the hearing loss to assist physical education teachers in their practice. This study aimed to develop and validate an educational material to subsidize the practice of physical education teachers in the activities with hard of hearing students. An instrument was built containing statements about the topics that could be addressed in the didactic material destined to the physical education teachers. The statements were followed by a Likert scale. The item was considered valid when it reached 80% index of agreement. The themes were evaluated by expert judges, from the fields of Speech Therapy (n=4), Pedagogy (n=2), and Physical Education (n=2). After that, it was drafted a preliminary version of the material, which was validated by the same judges and another two physical education teachers with experience with hard of hearing students. At this stage, the validation approached aspects related to the matter, language, illustrations, layout, motivation, and culture, which should reach an 80% of the agreement. Within ten themes proposed, nine were considered relevant . The item that was not validated referred to the use of figures with the Brazilian sign language - Libras. In the second stage of the study, the only items which have not achieved the minimum index of the agreement were related to the layout. The judges' suggestions were pertaining to the size of the font and background colors of some illustrations. The adjustments suggested by the judges were implemented. The design used in this study allowed to elaborate and to validate an educational material based on methodological criteria, containing objective information and illustrations which will be able to subsidize the work of physical education teachers in the performance with students with hearing loss.
Keywords: Physical education; Hearing impairment; Mainstreaming (Education)